-16+4=-32+26x

Simple and best practice solution for -16+4=-32+26x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+4=-32+26x equation:


Simplifying
-16 + 4 = -32 + 26x

Combine like terms: -16 + 4 = -12
-12 = -32 + 26x

Solving
-12 = -32 + 26x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26x' to each side of the equation.
-12 + -26x = -32 + 26x + -26x

Combine like terms: 26x + -26x = 0
-12 + -26x = -32 + 0
-12 + -26x = -32

Add '12' to each side of the equation.
-12 + 12 + -26x = -32 + 12

Combine like terms: -12 + 12 = 0
0 + -26x = -32 + 12
-26x = -32 + 12

Combine like terms: -32 + 12 = -20
-26x = -20

Divide each side by '-26'.
x = 0.7692307692

Simplifying
x = 0.7692307692

See similar equations:

| 6x+7=-143 | | 7+3x=2x-5(x-2) | | Q=180-2P | | f(x)=-4.9x^2+8x+1.8 | | lg(x-2)=5 | | 3x+5x+90+x=180 | | 6+34=-26+X | | 3y+2-y-6= | | 6x-4=15-58 | | 4(x+4)=3(2-2) | | Y=0.15x^2+153x | | R(x)=0.15x^2+153x | | R(x)=-0.15x^2+153x | | 27x^2+15x-28=0 | | 4x+16=6-6x | | 3(2x+5)=366 | | 8(x-4)-2(3x+6)= | | 3a(2a+4b)+2a(a-7b)= | | 450=10*5*h | | 4xy-10xy= | | 9x^2+15y^2-18x+12y-9=0 | | 480=10*b*8 | | px^2+(p+3)x+4=0 | | 4(x-4+8)= | | 5x*54=42(x-12) | | 5x*54=42x-12 | | 60=l*4*3 | | 12x^2+25= | | 50x-40(x-2)=90 | | 4x^2-16x+32= | | -2(y-7)-4= | | 13x+5(3-5x)= |

Equations solver categories